EFL Learners’ Willingness to Communicate, Language Learning Orientation, and Social Support in Kampung Inggris Pare - Saidah Saidah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract: this current study conducted to investigate any significant relationship among students’ willingness to communicate and language learning orientation as well as any significant relationship between students’ WTC and social support. It used quantitative design. There were 78 students participated in this study. They were studying English in Kampung Inggris Pare. For collecting the data, the students were asked to fill out three questionnaires; WTC questionnaire consist of 25 items, Language learning orientation questionnaire of20 items, and social support of 6 items. Pearson Product moment correlation was applied for calculating the data to know any possible correlation between the variables. From the data analysis showed that any significant correlation between students’ willingness to communicate and their language learning orientation. However, there was no any significant correlation between students’ WTC and social support. The result of the study showed that students’ language learning orientation is the best motivation for students to improve their English proficiency trough their willingness to communicate in regard to four English skills, speaking, reading, writing and comprehension. Although social support over all did not give significant correlation, some support from other friend and teacher positively correlated to students’ WTC in regard to speaking and writing skill. Keywords: Willingness to Communicate, Language Learning Orientation, Social Support